2014
DOI: 10.1177/0964663914521449
|View full text |Cite
|
Sign up to set email alerts
|

Activism and Legitimation in Israel’s Jurisprudence of Occupation

Abstract: Colonial law need not exclude the colonized in order to subordinate them, and ‘activist’ courts can advance the effect of subordination no less than ‘passive’ courts. As a case study, this article examines the jurisprudential legacy of the Israeli Supreme Court in the context of the prolonged Israeli occupation of Palestine. Applying insights from legal realist, law and society, and critical legal studies scholarship, the article questions the utility of using the activist and passive labels. It illustrates ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…From the story of the rise of judicial activism and of a liberal Court challenging the other branches of government and spreading the discourse of rights, some Israeli scholars exempt two major areas of judicial decisionmaking: cases dealing with the occupation of the West Bank and the Gaza Strip (Sheleff 1993), and cases dealing with the expropriation of lands from the Palestinian citizens (Holzman-Gazit 2007). Indeed, the Court limited only the excessive practices of the occupation regime, but not its ordinary operation (Kretzmer 2002), and legitimated its practices and overall structure (Shamir 1990;Sultany 2007Sultany , 2014. Likewise, the "constitutional revolution" left no significant marks on the land regime inside Israel and provided very few protections to Palestinian landholders (Holzman-Gazit 2007).…”
Section: The Limits Of Judicial Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the story of the rise of judicial activism and of a liberal Court challenging the other branches of government and spreading the discourse of rights, some Israeli scholars exempt two major areas of judicial decisionmaking: cases dealing with the occupation of the West Bank and the Gaza Strip (Sheleff 1993), and cases dealing with the expropriation of lands from the Palestinian citizens (Holzman-Gazit 2007). Indeed, the Court limited only the excessive practices of the occupation regime, but not its ordinary operation (Kretzmer 2002), and legitimated its practices and overall structure (Shamir 1990;Sultany 2007Sultany , 2014. Likewise, the "constitutional revolution" left no significant marks on the land regime inside Israel and provided very few protections to Palestinian landholders (Holzman-Gazit 2007).…”
Section: The Limits Of Judicial Interventionmentioning
confidence: 99%
“…The thin nature of the Court's ruling exemplified another hallmark of a minimalist court: The ruling consisted of four short paragraphs and did not explain the Court's conclusion concerning the permissibility of discrimination in this case. 21 "Political" Questions At the time the Court expanded its rhetoric of judicial review and intervened in the "nitty-gritty" politics (Barak-Erez 2002), it used occasionally the "political question" argument to avoid intervening in governmental decisions against Arab citizens (and also in petitions of Palestinians in the Occupied Territories, see Sultany 2002Sultany , 2014. This is especially striking, not only because it reveals the political judgment of the Court regarding when and where to intervene, but also because it shows the Court's unwillingness to intervene even when at face value the state's decision is flawed.…”
Section: Thin Rulingsmentioning
confidence: 99%
“…Kretzmer (2002: 19) has summarised this ambiguity stating that 'over the years Israeli governments pursued policies aimed at integration of the Occupied Territories with Israel while refraining from formally annexing the West Bank'. International law, and in particular the laws of armed conflict, has been used to facilitate Israeli control over the West Bank, giving rise to a 'legal hypocrisy' (Kretzmer, 2013) (Weill, 2015, Sultany, 2014, Kretzmer, 2002, Harpaz and Shany, 2010, the Israeli judiciary has substantially contributed to the situation. More generally, observers outside law have spoken of 'ethnocratic expansionism' by Israel over Palestine and Palestinians (Yiftachel, 2006: 3-9).…”
Section: A Regime Of Soft Boundariesmentioning
confidence: 99%
“…Shehadeh, 1985;Shamir, 1990;Sultany, 2014;Weill, 2015). David Kretzmer (2002: 2-3) has suggested that 'the main function of the Court has been to legitimize the government's actions in the Territories', both when the ISC/HCJ sides with the state authorities, and when it opposes them (also Shamir, 1990); as such, it plays a crucial role in maintaining and upholding the occupation (Kretzmer, 2002;Al-Haq, 2010;Harpaz and Shany, 2010: 515) alongside military courts (Dinstein, 2009: 132;Arai-Takahasi, 2009: 145-166).…”
Section: Introductionmentioning
confidence: 99%
“…Duncan's theoretical insights on the indeterminacy of the rights discourse and the limits and pitfalls of adjudication are useful in contexts like Palestine. 17 But Duncan's political contributions were not limited to academic discussions. Duncan never shied away from controversy and political debate.…”
Section: Duncan's Activism: Iraq Palestine Occupy!mentioning
confidence: 99%